Prevalence of Hemoglobin-S and Baseline Level of Knowledge on Sickle Cell Disease Among Pregnant Women Attending Antenatal Clinics in Dar-Es-Salaam, Tanzania - Tutuba, Hilda J.; Jonathan, Agnes; Lloyd, William; Luoga, Fredrick; Marco, Emanuela; Ndunguru, Joyce; Kidenya, Benson R.; Makani, Julie; Ruggajo, Paschal; Minja, Irene K.; Balandya, Emmanuel (Frontiers in Genetics, 2022)
Sickle cell disease (SCD) is the single most important genetic cause of childhood mortality globally. Newborn screening (NBS) is the recommended intervention aimed at early identification of babies with SCD and their linkage to care. To ensure success of NBS, pregnant women need to have the required knowledge on SCD and therefore motivation to screen their babies. The aim of this study was to determine the prevalence of hemoglobin-S and assess the baseline level of knowledge on SCD among pregnant women attending antenatal clinics in urban settings in Dar es Salaam, Tanzania. A cross-sectional study was conducted involving 600 pregnant women attending antenatal clinics at Buguruni health center, Mbagala hospital and Sinza hospital in Dar Es Salaam, Tanzania. Structured questionnaire was administered to all participants to assess socio-demographic characteristics and baseline level of knowledge on SCD, where those scoring 7 or higher out of 10 questions were considered to have good knowledge. 300 participants from two centers (Buguruni health center and Mbagala hospital) were subsequently screened for SCD using Sickle SCAN point-of-care test (BioMedomics Inc., USA). The data were analyzed using SPSS version 23. Pearson’s Chi-square was used to determine association between level of knowledge and socio-demographic factors. Multivariate logistic regression was used to ascertain the strength of associations. A two-tailed p-value < 0.05 was considered to be statistically significant. Of the 600 participants, majority were of the age between 26 – 35 years , with the parity 35 of 1-3 children and secondary level of education, while 56% were self-employed. Only 14.7% had good knowledge on SCD, only 2 (0.3%) knew their SCD status. Among 300 participants who were screened for SCD, 252 were Hb-AA (84%), 47 were Hb-AS (15.7%) and 1 (0.3%) was Hb-SS. Despite the high prevalence of hemoglobin-S among pregnant women attending antenatal clinics in urban settings in Tanzania, there is poor level of knowledge on SCD and personal knowledge of SCD status. Maternal screening and health education on SCD should be included as part of the comprehensive package for health promotion at antenatal clinics.